1977
DOI: 10.1007/bf00469735
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different fixatives and osmolality on the ultrastructure of the cochlear neuroepithelium

Abstract: To investigate which fixative is most suitable for the preservation of cochlear hair cells three main groups of fixatives were used: 1. 3% glutar aldehyde in various buffers (osmolality altered). 2. Glutar aldehyde/paraform aldehyde combination (ad modum Karnovsky). 3. Osmic acid solutions (OsO4) in veronal acetate buffer according to Rhodin (1954). The 2% osmic acid fixative (350--370mosm/kg) resulted in an excellent ultrastructural preservation; an acceptable result was obtained with a 3% glutar aldehyde fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The fixative has been shown to cause minimal shrinkage and distortion of the membranes of cells of the inner ear 17 . However, to verify that the major features we report here (rostral curvature and tenuous caudal suspension of the utricular maculae) were not due to shrinkage and/or other artifacts in histological processing, we confirmed these features in guinea pigs by direct visual observation with a high‐power operating microscope of the unfixed maculae in living anesthetized animals.…”
Section: Discussionsupporting
confidence: 76%
“…The fixative has been shown to cause minimal shrinkage and distortion of the membranes of cells of the inner ear 17 . However, to verify that the major features we report here (rostral curvature and tenuous caudal suspension of the utricular maculae) were not due to shrinkage and/or other artifacts in histological processing, we confirmed these features in guinea pigs by direct visual observation with a high‐power operating microscope of the unfixed maculae in living anesthetized animals.…”
Section: Discussionsupporting
confidence: 76%
“…First, the fixative used (phosphate‐buffered Karnovsky's) was specifically chosen because electronmicroscopic evidence has shown that the particular concentration used here caused minimal shrinkage of labyrinth membranes at the electronmicroscopic level. 9 Second, inspection of the maculae in living anesthetized animals confirms the orientation and curvature shown by the quantitative measures. In some anesthetized guinea pigs the inner ear was opened and the utricular and saccular macula were each visualized directly through the endolymph, and they showed similar patterns of curvature to the data presented here.…”
Section: Discussionmentioning
confidence: 55%
“…Guinea pigs were deeply anesthetized with nembutal and perfused with 400 mL of saline containing heparin followed by 500 mL of phosphate‐buffered Karnovsky's fixative (4% paraformaldehyde and 5% glutaraldehyde). 9 The head was mounted in a guinea pig stereotaxic apparatus (Kopf) and the inner ear of one labyrinth was dissected to show the maculae. The otoconia and otoconial membrane were very gently removed by a fine jet of saline.…”
Section: Methodsmentioning
confidence: 99%
“…The mor-to determine which could best preserve this tissue. Anniko and Lundquist (1977) and Park (1984) tested glutaraldehyde fixatives for mammalian and bird inner ears and concluded that the glutaraldehyde and the Karnovsky's fixative, i.e., a mixture of paraformaldehyde and glutaraldehyde, were satisfactory. They obtained a better result with a hyperosmolar fixative solution (> 1,500 mOsm) than with a hypoosmolar one.…”
Section: Discussionmentioning
confidence: 99%